2022
DOI: 10.3390/jpm12071108
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Brain Injury and Spinal Cord Injury Management Strategies: A Narrative Review

Abstract: Spinal cord injury (SCI) is a catastrophic event with multiple comorbidities including spastic paralysis, sensory loss, autonomic dysfunction with sympathetic blunting, neurogenic orthostatic hypotension, neurogenic restrictive and obstructive lung disease, neuropathic pain, spasticity, neurogenic bladder, neurogenic bowel, immobilization hypercalcemia, osteopenia/osteoporosis, neurogenic obesity, and metabolic dysfunction. Cervical and thoracic SCI is all too often accompanied by traumatic brain injury (TBI),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…The incidence of constipation ranges from 32 to 41%, with an index at discharge of approximately 20%. Only one study reported a patient with a double diagnosis of SCI and ABI ( Valbuena Valecillos et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of constipation ranges from 32 to 41%, with an index at discharge of approximately 20%. Only one study reported a patient with a double diagnosis of SCI and ABI ( Valbuena Valecillos et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study reported a patient with a double diagnosis of SCI and ABI that increased from 7 to 74% according to different criteria ( Valbuena Valecillos et al, 2022 ). The dissociation between parasympathetic and ENS can contribute to NBD in patients with SCI or traumatic brain injury (TBI; Blanke et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Consistent with previous reports, motor vehicle crashes accounted for 44.4% of patients with concomitant TBI and tSCI. 22 This is to be expected given the significant force associated with this mechanism of injury. This pattern differed from patients with tSCI without TBI, who were more frequently admitted to the hospital after falls (51.2%).…”
Section: Discussionmentioning
confidence: 96%